Stable Single-Longitudinal-Mode Erbium Fiber Ring Laser Utilizing Self-Injection and Saturable Absorber - Chien-Hung Yeh; Tzu-Jung Huang; Zi-Qing Yang; Chi-Wai Chow; Jing-Heng Chen (IEEE Photonics Journal)
In this work, we demonstrate a wavelength-tunable erbium-doped fiber (EDF) ring laser with stable single-longitudinal-mode (SLM) output. Here using the self-injection method and unpumped EDF-based saturable absorber can suppress other densely side-mode to achieve SLM. Hence, the output power and optical signal-to-noise ratio of proposed EDF ring laser are between −7.1 and 2.1 dBm and 30.1 and 36.5 dB in the tuning range of 1525.0 to 1574.0 nm, respectively. According to the proposed EDF laser structure, the wavelength operation range can extend to shorter L-band from C-band. Moreover, the output stability of the proposed EDF ring laser is also executed experimentally.